Developing a Web-Based Mobile Game to Enhance Students’ Motivation in learning English Vocabulary - Nurpita; Edhy Rustan; Masruddin; Wisran (Institut Agama Islam Negeri Palopo, 2025)
This study investigated the effectiveness of web-based mobile games in enhancing students' motivation and vocabulary acquisition in English language learning. The research was conducted with seventh-grade students at SMPN 7 Palopo. This study aimed to investigate the effectiveness of web-based mobile games in enhancing students' motivation and vocabulary acquisition in English language learning. A research and development (R&D) approach using the ASSURE model was employed. The study found that traditional teaching methods often resulted in disengagement and hindered vocabulary learning. To address this issue, a web-based mobile game platform, Wordwall, was implemented. The findings revealed that students preferred more interactive learning methods and that Wordwall significantly improved their motivation and vocabulary mastery. The study concludes that developing web-based mobile games can be a successful strategy for enhancing English language learning.